Effect of Hydroxyquinoline on Preparation of Chromosome Roots and Garlic Garlic (Allium sativum L.) - Arbaul Fauziah (Natural B, Journal of Health and Environmental Sciences, 2015)
The effective method in making chromosome prepararation was able to count the number of chromosome easier, especially for analysis the ploidy level in plants. Garlic (Allium sativum L.) is one of the plants that the chromosome is difficult to be counted because their chromosomes are long and difficult to spread during the squashing. This research was to find out the effect of hydroxiquinoline on making chromosome preparation of root and callus in garlic. The steps of making chromosome preparation were fixation in Farmer’s fluid, put in hydroxiquinoline for an hour, hydrolysis in 1N HCl for two minutes at 60°C, put in Carnoy for 30 minutes, and stained in 1% aceto orcein for 20 minutes. The treatment were gift hydroxiquinoline for an hour after put in fixative fluid and the control were making preparation without gift hydroxiquinoline. The result of this research suggest that the method of making preparation by treatment with hydroxiquinoline for an hour after fixation produced the chromosomes that the stain were sharp and contrast, and also it produced well spread chromosomes that were clearly defined of both callus and root tip in garlic.